POTENSI DAN PERMASALAHAN PENGEMBANGAN PERKEBUNAN KELAPA SAWIT SKALA BESAR DI KALIMANTAN TIMUR - Adhynugraha, Santo (Pusjar SKPP Lembaga Administrasi Negara, 2006)
East Kalimantan is one of wealthiest and widest provinces in Indonesia having strategic position, either geographically or economically. It is characterized by prosperous natural resources such as vast deposit of mining and energy, oceanic and forest resources, and so forth. As a well-off province, good and sound management is truly required to improve public prosperity as well as to guard ecological quality. One of the most probable potency is palm oil plantation. The availability of bountiful land in Kalimantan makes the efforts of building large-scale palm oil plantation more reliable. However, discourse on the operation of the one-million-hectare-palm-oil-plantation is awfully dilemmatic. There is no symmetric concordance between ‘pros’ and ‘cons’ so far. The government policy on promoting plantation sector, therefore, is still blurred. Based on such situation, this paper tries to explore and evaluate the government plan to develop large-scale oil palm plantation in East Kalimantan province, especially from the perspective of public policy. Keywords: kebijakan, kelapa sawit, Kalimantan Timur.